Pengaruh Meditasi Terhadap Tingkat Kecemasan dengan Pengukuran HRV Berbasis Sensor MAX30102 - Bacilius Agung Suburdjati; Lisda Sukoco; Claire Gretchen Tjandraprawira; Brenda Orvala Lawantara (Jurnal Sistem Informasi Galuh, 2026)
This study aims to analyze the effect of an intervention (meditation sessions) on subjects’ anxiety levels, which were objectively measured through Heart Rate Variability (HRV) using the MAX30102 sensor. Anxiety has become an increasingly dominant mental health issue in modern society, creating the need for non-pharmacological and measurable intervention methods. The study employed a One Group Pretest-Posttest Design involving six subjects, in which physiological indicators (BPM, SDNN, RMSSD, SpO2, and HRV) were measured before and after the intervention. Statistical results showed a significant effect of meditation on the autonomic nervous system. The subjects’ average heart rate (BPM) decreased by 19%, with a Cohen’s d effect size of -2.53, indicating a very large effect in reducing stress responses. There was also a significant increase in HRV, as demonstrates that meditation is physiologically effective in improving subjects’ resilience to stress. The combination of the MAX30102 sensor technology and HRV analysis provides a valid tool for monitoring and managing anxiety.